Influence of Blended Learning Against Computational Thinking Students on Basic Programming Subjects is Reviewed From Self-Efficacy Students - Hakim, Zaima Faiza; Munoto, Munoto; Buditjahjanto, I.G.P.Asto; Rijanto, Tri (International Journal for Educational and Vocational Studies, 2020)
The study aims to know the computational thinking students who are taught using blended learning and students taught using a direct learning model. To find out the thinking of students with self-efficacy owned by students . This type of research is experimental research using factorial design. The results of the study found that (1) Computational thinking students taught using blended learning are higher than the computational thinking students taught using direct learning models; (2) Computational thinking students with self-efficacy higher height than computational thinking students with self-efficacy low on the basic programming subjects; and (3) There is an interaction between learning models (blended learning and direct learning models) and self-efficacy against computational thinking students in basic programming subjects.